Aesthetic, Communicative and Symbolic Representation of the Philosophical Underpinnings of Akan (Akwapem) Proverbs - KQUOFI, STEVE; SARBAH, GEORGE TETTEH; Arthur, Nana Ama Pokua (Advances in Social Sciences Research Journal, 2015)
Proverbs, as an integral part of African art and culture, are imbued with significant philosophical and communicative values that give meanings to their aesthetic quality as well as enhance their practical application for co-existence. The people of Akan Akuapem are blessed with unique philosophies in terms of proverbs and symbolism that seek to shape the youth and prepare them for a better future. This language of proverbs teaches, guides and, to a large extent, adorns relationships. The study employed a qualitative and visual research methodology. Symbolic communication and interactive activities were used to select 25 proverbs, which have been represented in abstract symbols. The study revealed great interests of the Akuapem youth in the philosophical underpinnings and symbolic communicative dynamics of Akwapem proverbs as the bedrock of Akan culture. In the quest to promote and preserve these opportunities on proverbs and symbolism as a tool for cultural development, there is the need to educate frequently the youth, both formally and informally, on the uses as well as the effects of these proverbs and symbols on society as a whole.